Internalization of Ethical Values in Women’s Prayer Gatherings: A Living Quran Study - Mery Agustina; Hery Sahputra (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
This study examines the internalization of ethical values in religious gatherings within Muslim women’s prayer communities, analyzed through the Living Quran perspective. Using a descriptive qualitative method, data were collected through participatory observation, in-depth interviews, and documentation involving active participants. The findings indicate that ethical principles such as providing space for others, maintaining courtesy, showing respect, and attentive listening are consistently practiced in these gatherings. Although most participants are not explicitly aware of the textual source of these values, they have been deeply embedded in social behavior and religious traditions. The prayer gatherings serve not only as a medium for spiritual enrichment but also as a space for character formation, strengthening social bonds, and enhancing communal faith. This study underscores the role of local religious traditions as effective vehicles for transmitting Quranic values in socially meaningful and practical ways within Muslim communities.